2008
DOI: 10.1007/s00404-008-0750-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary dysmenorrhea in young adult female university students

Abstract: Prevalence of primary dysmenorrhea was found higher than that cited in the literature. It was established that although the rate of consultation with health professionals about menstruation and related changes was low, use of agents known to be effective in primary dysmenorrhea treatment was highly common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
74
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 13 publications
19
74
2
4
Order By: Relevance
“…In the women's group in our study, the mean age at menarche (13.2±1.3) and menopause (46.4±5.9) was similar to that of the general population in Turkey (16,17,18,19). Current irregularities of the menstrual cycle were found in 15.1% of our sample, and all irregularities had begun after starting drug use.…”
Section: Reproductive Functionssupporting
confidence: 80%
“…In the women's group in our study, the mean age at menarche (13.2±1.3) and menopause (46.4±5.9) was similar to that of the general population in Turkey (16,17,18,19). Current irregularities of the menstrual cycle were found in 15.1% of our sample, and all irregularities had begun after starting drug use.…”
Section: Reproductive Functionssupporting
confidence: 80%
“…[4,5,6,7] In the study by Polat et al, [7] the prevalence of dysmenorrhea was 72.7%. 66.2% suffered from severe and moderate dysmenorrhea which was similar to the study by Burnett et al [4] In the study conducted on 432 nurses by Chaya Chinda C et al, [8] the prevalence of dysmenorrhea was 25.1%.…”
Section: Discussionmentioning
confidence: 95%
“…Family history of dysmenorrhea had higher prevalence of dysmenorrhea which is consistent with many studies in literature. [7] Balbi C et al [13] noted that a higher consumption of fish, eggs, fruit and a lower consumption of wine is correlated with a lower frequency of dysmenorrhea. He observed that early menarche was related to increase in the prevalence and severity of dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Menstruation disturbances of young adults have been found worldwide (Montero et al, 1996;Nicodemus et al, 2001;Hirata et al, 2002;Weller and Weller, 2002;Adams and Deitch, 2005;El-Gilany et al, 2005;Järvelaid, 2005;Anastasakis et al, 2008;Jahromi et al, 2008;Loto et al, 2008;Singh et al, 2008;Agarwal and Venkat, 2009;Chang and Chen, 2009;Farquhar et al, 2009;Ogunfowokan and Babatunde, 2010;Ozerdogan et al, 2009;Polat et al, 2009;Yamamoto et al, 2009;etc. ).…”
Section: Introductionmentioning
confidence: 99%